Financial spillovers to emerging markets during the global financial crisis - Frank, Nathaniel; Hesse, Heiko (IMF working paper, 2009)
In this paper potential financial linkages between liquidity and bank solvency measures advanced economies and emerging market (EM) bond and stock markets are analyzed the latest crisis. A multivariate GARCH model is estimated in order to gauge the extent of co-movements of these financial variables across markets. The findings that the notion of possible de-coupling (in the financial markets) had been misplaced. EM stock markets reached their peak in the last quarter of 2007, interlinkages between funding stress and equity markets in advanced economies and EM financial indicators highly correlated and have seen sharp increases during specific crisis moments.